Culture‐inappropriate antibiotic therapy decreases quality of life improvement after sinus surgery. Issue 5 (10th January 2014) - Zhang, Zi; Palmer, James N.; Morales, Knashawn H.; Howland, Timothy J.; Doghramji, Laurel J.; Adappa, Nithin D.; Chiu, Alexander G.; Cohen, Noam A.; Lautenbach, Ebbing
<x xml:space="preserve">Abstract</x> Background Despite their widespread use, antibiotics have not been shown to improve chronic rhinosinusitis (CRS) outcomes. We aimed to determine whether culture‐inappropriate postoperative antibiotic therapy was associated with less quality‐of‐life (QOL) improvement following functional endoscopic sinus surgery (FESS). Methods This retrospective cohort study recruited 376 adult CRS patients undergoing FESS between October 1, 2007 to December 31, 2011. Patient demographics, comorbidities and medications were collected at baseline. Trimethoprim‐sulfamethoxazole and clindamycin were administered for 2 weeks postoperatively. The antibiotic appropriateness was determined based on bacterial resistance profile of organisms identified during intraoperative culture. The QOL outcome was defined as change of 22‐item Sinonasal Outcome Test scores from preoperative visit to 1‐month, 3‐month, and 6‐month post‐FESS. Clinically significant difference was defined as at least 0.5 standard deviations (SD) of baseline QOL score in the reference group. Mixed‐effects regression models were performed. Results Seven percent of patients (n = 27) had culture‐inappropriate antibiotic therapy, and additional 5% (n = 19) had culture‐specific antibiotic adjustment. Compared to patients with culture‐appropriate antibiotics, patients with culture‐inappropriate antibiotics had significantly less improvement of QOL from baseline to postoperative 1‐month and 3‐month follow‐up where the difference became clinically significant; patients with antibiotic adjustment had more QOL improvement from baseline to 1‐month follow‐up, but their QOL worsened at 3‐month follow‐up, and these changes were not clinically significant. However, all effects washed out at 6‐month follow‐up with no significant differences. Conclusion Culture‐inappropriate postoperative antibiotic therapy decreased short‐term QOL improvement to a clinically meaningful level after FESS. Culture guided selection of antibiotics may improve short‐term FESS outcome.